Large field ranges from aligned and misaligned winding - Hebecker, Arthur; Junghans, Daniel; Schachner, Andreas (Journal of high energy physics, 2019)
We search for effective axions with super-Planckian decay constants in type IIB string models. We argue that such axions can be realised as long winding trajectories in complex-structure moduli space by an appropriate flux choice. Our main findings are: the simplest models with aligned winding in a 2-axion field space fail due to a general no-go theorem. However, equally simple models with misaligned winding, where the effective axion is not close to any of the fundamental axions, appear to work to the best of our present understanding. These models have large decay constants but no large monotonic regions in the potential, making them unsuitable for large-field inflation. We also show that our no-go theorem can be avoided by aligning three or more axions. We argue that, contrary to misaligned models, such models can have both large decay constants and large monotonic regions in the potential. Our results may be used to argue against the refined Swampland Distance Conjecture and strong forms of the axionic Weak Gravity Conjecture. It becomes apparent, however, that realising inflation is by far harder than just producing a light field with large periodicity.
Gesehen am 01.08.2019